2007
DOI: 10.1007/s10338-007-0720-2
|View full text |Cite
|
Sign up to set email alerts
|

The periodic crack problem in bonded piezoelectric materials

Abstract: The problem of a periodic array of parallel cracks in a homogeneous piezoelectric strip bonded to a functionally graded piezoelectric material is investigated for inhomogeneous continuum. It is assumed that the material inhomogeneity is represented as the spatial variation of the shear modulus in the form of an exponential function along the direction of cracks. The mixed boundary value problem is reduced to a singular integral equation by applying the Fourier transform, and the singular integral equation is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…2. Based on Von Mises strain distribution [72], it is found that the abrupt drop of force-displacement curve corresponds to different dislocation activities [73]. A number of inflection points of interest are denoted by alphabetic characters in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2. Based on Von Mises strain distribution [72], it is found that the abrupt drop of force-displacement curve corresponds to different dislocation activities [73]. A number of inflection points of interest are denoted by alphabetic characters in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The differential quadrature(DQ) method is a powerful tool for dealing with dynamical problems. It was introduced for structural analysis by Bert [7] , and since then it has been successfully employed for the analysis of vibration of beams [8][9] . In the present work, using the DQ method , the natural frequencies are analyzed.…”
Section: Introductionmentioning
confidence: 99%